2004
DOI: 10.2214/ajr.183.3.1830629
|View full text |Cite
|
Sign up to set email alerts
|

Extraaxial Neurofibromas Versus Neurilemmomas: Discrimination with MRI

Abstract: MRI shows features helpful for differentiating extraaxial neurofibromas from neurilemmomas; however, no single finding or combination of findings allows definitive differentiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
83
2
7

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(97 citation statements)
references
References 13 publications
5
83
2
7
Order By: Relevance
“…However, in our study, none of the cases showed the target sign, which was probably related to the frequent cystic changes in schwannomas that were intradural extramedullary in location. The fascicular sign manifests as multiple small ring-like structures with a high signal intensity in the background on T2-weighted images, and is more frequently observed in schwannomas than in neurofibromas (2). Only four cases in our study (23.52%) showed the fascicular sign, but it was not as definite as that in their peripheral counterparts.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…However, in our study, none of the cases showed the target sign, which was probably related to the frequent cystic changes in schwannomas that were intradural extramedullary in location. The fascicular sign manifests as multiple small ring-like structures with a high signal intensity in the background on T2-weighted images, and is more frequently observed in schwannomas than in neurofibromas (2). Only four cases in our study (23.52%) showed the fascicular sign, but it was not as definite as that in their peripheral counterparts.…”
Section: Discussioncontrasting
confidence: 55%
“…2). The target sign was described in T2-weighted MRI findings of neurogenic tumors (2,8), which was characterized by a low signal intensity centrally and a high signal intensity peripherally, and it was seen more frequently in neurofibromas (50-70%) than in schwannomas (50%) (2). However, in our study, none of the cases showed the target sign, which was probably related to the frequent cystic changes in schwannomas that were intradural extramedullary in location.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…Jee et al 15 reported that the presence of target signs on T 2 WIs suggests a high probability of neurofibromatosis, although a fascicular appearance and thin hyperintense rim were also detected in some cases. On the other hand, Koga et al 12 suggested that the target sign predominantly suggests the possibility of a schwannoma.…”
Section: Discussionmentioning
confidence: 99%
“…Fibromatosis is usually hypointense on T 2 weighted images but may also show heterogeneous hyperintensity, reflecting marked cellularity or myxoid tissue. Neurogenic tumours are characterised by the entry and exit of nerves [11].…”
Section: Discussionmentioning
confidence: 99%